2020
DOI: 10.1186/s12879-020-05301-2
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of herpes simplex virus type 1 among people living with HIV in Mbeya, Tanzania

Abstract: Background: Despite the significant decline in the prevalence of HIV in Tanzania, the prevalence rates in Mbeya, Iringa, and Njombe regions are higher than the national average and have remained stable for years. The current stable HIV prevalence may be driven by factors such as a high incidence of sexually transmitted infections (STIs) and high-risk behaviours. In sub-Saharan Africa, it has previously been observed that up to 50% of HIV cases were attributed to herpes simplex type 2 (HSV-2) among low-risk pop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In this study, the HSV-1 seroprevalence (76.8%) was lower than the previous reports from India (77.25%) 11 and Tanzania (83.2%). 12 Nonetheless, it was higher than the prevalence reported by Wani et al 13 from India (73%) and Yunusa et al 14 from Nigeria (63.6%). The HSV-2 seroprevalence of 56.2% found in this study was higher than the previous studies from India (39.91%, 30.4%), 11 13 Nigeria (36.4%) 14 and Tanzania (18%), 15 although lower than the reports from Ukraine (68%) 16 and Canada (86%).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In this study, the HSV-1 seroprevalence (76.8%) was lower than the previous reports from India (77.25%) 11 and Tanzania (83.2%). 12 Nonetheless, it was higher than the prevalence reported by Wani et al 13 from India (73%) and Yunusa et al 14 from Nigeria (63.6%). The HSV-2 seroprevalence of 56.2% found in this study was higher than the previous studies from India (39.91%, 30.4%), 11 13 Nigeria (36.4%) 14 and Tanzania (18%), 15 although lower than the reports from Ukraine (68%) 16 and Canada (86%).…”
Section: Discussionmentioning
confidence: 55%
“…This was consistent with a previous study from Nigeria. 14 However, Issakwisa et al 12 from Tanzania did not find any significant association between the seroprevalence of HSV-1 with the gender of patients with HIV. However, for HSV-2 seroprevalence, no significant difference was found between two genders.…”
Section: Discussionmentioning
confidence: 91%
“…to 24-year-old individuals in Eastern Africa and from 46% to 66% in high-risk populations [14,15]. Sexually acquired genital HSV-1 infections are common in young females and males with active sex lives [16]. According to Issakwisa et al [16], the infection rates are higher in males than in females [16].…”
Section: Discussionmentioning
confidence: 99%
“…Sexually acquired genital HSV-1 infections are common in young females and males with active sex lives [ 16 ]. According to Issakwisa et al [ 16 ], the infection rates are higher in males than in females [ 16 ]. Our study also showed that HSV-1 infection was more common in males than in females.…”
Section: Discussionmentioning
confidence: 99%